Peran Etika Kerja Islami sebagai Pemoderasi Pengaruh Kepemimpinan Transformasional terhadap Organizational Citizenship Behavior dimediasi oleh Kepercayaan - Arifiani, Ratya Shafira; Rumijati, Aniek (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2021)
This study aim s to analyze the direct and indirect effects of the transformational leadership and organizational citizenship behavior. Accordingly, it needs to add the mediating variables , namelythe trust and I slamic work ethic in order to evaluating the effects of moderation. The object of this study (population) is all members of staff at the syariah rooms, one of the guest house in Malang. This study instrumentalizes the probabilty sampling technique in dealing with a total sample of 50 respondents. Meanwhile, t he data analysis of this study is the path analysis . Th is study finds that the transformational leadership seems to have no effects on the o rganizational c itizenship b ehavior, but on trust . In this context, the trust has had an effect on theo rganizational citizenship behavior and has mediated the effect of transformational leadership on o rganizational c itizenship b ehavior .The Islamic work ethics has had no moderat ion effect o nthe transformational leadership o fthe o rganizational c itizenship b ehavior. Although the result of this study seems to be specific, it needs to be supported by the larger scale of study and advancement of the research variable in order to find larger patterns of study in the similar field.